Regional integration of long-term national dense GNSS network solutions - Ambrus Kenyeres; J. G. Bellet; C. Bruyninx; A. Caporali; F. de Doncker; B. Droscak; A. Duret; P. Franke; I. Georgiev; R. Bingley; L. Huisman; L. Jivall; et al. (GPS Solutions, 2019)
The EUREF Permanent Network Densification is a collaborative effort of 26 European GNSS analysis centers providing series of daily or weekly station position estimates of dense national and regional GNSS networks, in order to combine them into one homogenized set of station positions and velocities. During the combination, the station meta-data, including station names, DOMES numbers, and position offset definitions were carefully homogenized, position outliers were efficiently eliminated, and the results were cross-checked for any remaining inconsistencies. The results cover the period from March 1999 to January 2017 (GPS week 1000-1933) and include 31 networks with positions and velocities for 3192 stations, well covering Europe. The positions and velocities are expressed in ITRF2014 and ETRF2014 reference frames based on the Minimum Constraint approach using a selected set of ITRF2014 reference stations. The position alignment with the ITRF2014 is at the level of 1.5, 1.2, and 3.2 mm RMS for the East, North, Up components, respectively, while the velocity RMS values are 0.17, 0.14, and 0.38 mm/year for the East, North, and Up components, respectively. The high quality of the combined solution is also reflected by the 1.1, 1.1, and 3.5 mm weighted RMS values for the East, North, and Up components, respectively.

Erratum to: Influence of different GPS receiver antenna calibration models on geodetic positioning - Q. Baire; C. Bruyninx; J. Legrand; E. Pottiaux; W. Aerts; P. Defraigne; N. Bergeot; J. M. Chevalier (GPS Solutions, 2016)

Influence of different GPS receiver antenna calibration models on geodetic positioning - Q. Baire; C. Bruyninx; J. Legrand; E. Pottiaux; W. Aerts; P. Defraigne; N. Bergeot; J. M. Chevalier (GPS Solutions, 2014)

Impact of the Halloween 2003 ionospheric storm on kinematic GPS positioning in Europe - N. Bergeot; C. Bruyninx; P. Defraigne; S. Pireaux; J. Legrand; E. Pottiaux; Q. Baire (GPS Solutions, 2011)

Higher-order ionospheric effects in GPS time and frequency transfer - S. Pireaux; P. Defraigne; L. Wauters; N. Bergeot; Q. Baire; C. Bruyninx (GPS Solutions, 2010)

On the link between GPS pseudorange noise and day-boundary discontinuities in geodetic time transfer solutions - P. Defraigne; C. Bruyninx (GPS Solutions, 2007)

EPN coordinate time series monitoring for reference frame maintenance - A. Kenyeres; C. Bruyninx (GPS Solutions, 2004)